Penerapan Project Based Learning (PBL) dengan Strategi Praktik Tugas Kelompok (PTK): Untuk Meningkatkan Aktivitas Belajar IPA Materi Struktur Organisasi Kehidupan dalam Kondisi Pandemi Covid-19 Pada Siswa Kelas VII-A SMP Negeri 4 Sakti T.P 2021/2022 - Marjuani, Cut (Journal of Technology and Literacy in Education, 2024)
This study aims to improve science learning activities in the Covid-19 pandemic through project based learning with group assignment practice strategies. This research method uses classroom action research. The subjects of the study were 33 students of class VII-a of SMP Negeri 4 Sakti. The research instruments used observation sheets, questionnaires, and documentation. The collected data were then analyzed descriptively. The results of this study indicate that in cycle I.1, data was obtained of 55.8% and in cycle I.2, an average value of 65.5% was obtained, while in cycle II, an average value of 85.45% was obtained. In cycle I, students were still said to be not active in participating in the learning process, while in cycle II, students were stated to be more active in carrying out the learning process. So it can be concluded that students are more active in carrying out science learning using the project based learning model with group assignment practice strategies on the material on the structure of the organization of life in the Covid-19 pandemic conditions at SMP Negeri 4 Sakti.